Computational analysis of fluid dynamics and heat transfer characteristics of a vibrating heated plate - Pilli, A.; Abishek, S.; Narayanaswamy, Ramesh; Jewkes, J.; Lucey, A.; Narayanan, V. (2014)
The introduction of vibrations to a horizontal plate can induce turbulence in the flow field adjacent to the plate under certain combinations of amplitudes and frequency. It is also known that beyond a threshold level of heating, the convective flow field over a heated plate will transition to turbulence. The characterization of the flow field with turbulence in the domain is of paramount importance to ensure a realistic simulation of the flow physics. In the present study, a computational analysis is carried out to characterize the flow regime over a transversely vibrating flat plate (unheated and heated) into laminar or turbulent. The range of frequency and amplitudes of vibrations considered for this analysis are 0-150 Hz and 0-2 mm respectively. Three different models viz. laminar; Reynolds Averaged Navier-Stokes (RANS) approach with k-? SST model; and Large-Eddy Simulations (LES) approach with dynamic Smagorinsky-Lilly model are employed, and the results of local, time and space averaged wall shear stress, and the Nusselt number are compared. It has been found that under conditions with unheated or heated vibrating plate, the wall shear stress predictions by all three models are in good agreement with each other with a maximum deviation of 9.5 %. However, when the predictions of local Nusselt number on the heated vibrating plate are compared, it is found that the laminar and LES predictions are in good agreement with each other; the k-? SST model predictions deviate significantly from the other two models.